Acute Motor Axonal Polyneuropathy Following Mumps Infection in a 9-Year-Old Girl. (12th April 2018) - Pediredla, Karunakar; Abimannane, Anitha; Chandrasekaran, Venkatesh; Jagadisan, Barath; Biswal, Niranjan
Abstract: A 9-year-old girl presented with lower motor neuron type of paralysis involving limbs, trunk and multiple cranial nerves (7, 9 and 10) with preceding history of mumps 1 week before the onset of weakness. There were no features to suggest either a meningitis or encephalitis in the child. Cerebrospinal fluid showed hypoglycorrhachia and mild protein elevation; magnetic resonance imaging of the brain was normal. Nerve conduction study showed motor axonal neuropathy. Serology for mumps IgM was positive, consistent with a diagnosis of post-mumps acute motor axonal polyneuropathy. The girl made a complete recovery within 3 weeks.